The effect of concentration variation of ethanolic extract from potato peels (Solanum tuberosum L.) on the physical properties and antibacterial activity of gels against Propionibacterium acnes - Rashati, Dewi; Eryani, Mikhania Cristiningtyas (Pharmaciana, 2018)
Gel is a semisolid dosage form that consumers prefer because of its cool sensation. This research aimed to identify the effect of different concentrations of ethanolic extract from potato peels on the physical properties and the antibacterial activities of the resultant gels against Propionibacterium acnes. The gel was prepared with three formulas using a variety of potato peel concentrations, namely 50%, 60% and 70%. Its physical properties were analyzed based on organoleptic observation, homogeneity, pH, and spreadability. The results showed that the ethanolic extract of potato peels affected the color and viscosity of the gel. However, no effects were detected on shape, smell, pH, and spreadability. All formulas showed strong inhibitory capacity against Propionibacterium acnes.